Low cycle fatigue damage model and sensitivity analysis of fatigue crack initiation by finite element approach (Fracture and Structural Integrity, 2020)
To meet the design requirements, different types of defects are often machined on the surface of fatigue components. Local stress concentration formed at the notch accelerate the initiation of fatigue crack, therefore greatly shorten the service lives of such components. Based on the theory of continuous damage mechanics and the principle of irreversible thermodynamics, the damage evolution model of low cycle fatigue is investigated. By programming the damage evolution model as UMAT subroutine and coupling it to ABAQUS, the fatigue damage and crack initiation life of notched P92 steel samples under specific loads are simulated, and the crack initiation location is determined. Furthermore, the damage evolution and crack initiation sensitivity of notch morphology are considered. The results show that the crack initiation occurs easily in the notch root where the damage is greatest and the plastic strain accumulates fastest under cyclic loading. The fatigue damage accumulates slowly at the initial stage, but the damage accumulates rapidly after the cumulative damage reaches a critical value. The fatigue damage evolution and fatigue initiation life are very sensitive to the notch morphology parameters. The notch morphology need to be carefully analyzed, to improve the fatigue life of the notched samples.
Keywords: Defect; damage evolution model; Low cycle fatigue; Crack initiation; Sensitivity